'Volumetric analysis of hand and rotary root canal instrumentation and filling in primary teeth using Spiral Computed Tomography' – an invitro study. Issue 3 (4th July 2015) - Poornima, Parameswarappa; Disha, Patil; Nagaveni, Nandanhosur Basavanthappa; Roopa, KirishettaR Basavaraj; Bharath, Kashetty Panchakshari; Neena, Indavara Edagunji
Abstract : Aim: To compare and evaluate the volumetric analysis of pre‐ and post‐root canal instrumentation in primary teeth using hand and rotary files and also to analyse the volume of root canal filling. Materials and methods: A total of 20 primary teeth were divided into two groups randomly and subjected to spiral computed tomography (SCT) analysis before and after instrumentation. For manual technique (Group 1), teeth were prepared using K files and rotary (Group 2) preparation was performed with Mtwo files. Volumetric enlargement was calculated using Osirix software. Root canals were then filled with rotary lentulospiral using zinc oxide–eugenol cement (ZOE). The filled volume in each canal was measured using SCT and the percentage of obturated volume was calculated. The data were statistically analysed using paired t‐ tests. Results: There was a statistically significant difference in the volume of root canal enlarged in both the groups. Rotary files showed significant increase in the volume compared to K files. Mtwo instrumented root canals showed good obturated volume compared to manual technique, although voids were common in both the groups. Conclusion: Rotary root canal instrumentation may be indicated for utilization in primary teeth, for enhancing root canal preparation and good quality of root canal filling.